Cigarette taxes, prices, and disparities in current smoking in the United States - Lucie Kalousova; David Levy; Andrea R. Titus; Rafael Meza; James F. Thrasher; Michael R. Elliott; Nancy L. Fleischer (Elsevier, 2020)
Increasing cigarette taxes has been the cornerstone of tobacco control policy. Recent work has argued that raising cigarette taxes alone may no longer be an effective strategy for lowering smoking rates. We largely confirm these findings but also find that increases in price continue to predict lower smoking participation in most model specifications. We argue that raising cigarette prices via taxation remains an effective public health policy. We discuss the advantages of homogeneous tax environments and minimum price laws for eliminating opportunities for consumers to offset tax increases by searching for lowest taxes.